Cerca de la revolución: Uruguay, el semanario Marcha y la integración latinoamericana (1958-1959) - Ximena Espeche (Nuevo mundo - Mundos Nuevos, 2011)
It is well known that the Cuban revolution was a particular moment that brought many political and cultural changes. In this paper I explore how the important Uruguayan review Marcha - which in the 60s became internationally relevant - revised its traditional topics under the light of the revolution: anti-imperialism, Latin American integration and the defense of democracy. I analyze a short period in which the Cuban revolution did not mean what it was going to mean soon. This allows me to examine at Marcha the transformation and redefinition process of the revolution’s meanings. The reception of the revolution experience was related to the questions about Uruguay as an exceptional country in Latin America. Specifically in a period that has been considered one of an “structural crisis” that could affect Uruguayan viability.